Absence management of migrant agency workers in the food manufacturing sector. Issue 10 (30th May 2016) - Hopkins, Benjamin; Dawson, Chris; Veliziotis, Michail
Abstract : Temporary workers in low-skilled roles often experience 'hard' HRM practices, for example the use of the Bradford Factor to monitor absence, rather than using incentives to reward attendance. However, this peripheral workforce has become increasingly diverse in the UK since the A8 European Union expansion, which has seen over a million migrants from central and eastern Europe register to work in the UK. Importantly, there is also heterogeneity within this group of workers, for example between those who intend to migrate for a short period of time then return, and those who are more settled and wish to develop a career. By considering the particular case of absence management, this paper examines how these different groups of migrants respond to HRM practices. The key contribution of the paper is to examine how different groups of migrants experience these practices, rather than simply comparing migrant and native workers as two homogeneous groups. The paper presents data from the food manufacturing sector in the UK. In total, 88 semi-structured interviews were conducted with operations managers, HR managers, union convenors and workers on permanent, temporary and agency contracts. In addition, data from informal interviews and observation at five companies are presented.